ANALISIS KINERJA PEGAWAI PADA KANTOR DESA LOLIBU KABUPATEN BUTON TENGAH - Titien Rahayuningsih; Abd. Azis Muthalib; Kornelia Oba (STIE ENAM ENAM KENDARI, 2025)
This research aims to examine and analyze the performance of employees at the Village Office of Lolibu, Central Buton Regency. The type of data used in this study is qualitative data. Data collection techniques employed include interviews and documentation. The data analysis technique utilized is qualitative descriptive analysis. The findings of this research indicate that the performance of employees at the Village Office of Lolibu, Lakudo District, Central Buton Regency is considered good. This is evidenced by effective employee performance measured through three key indicators: service quality, responsiveness, and accountability. In terms of service quality, employees provide clear, prompt, and friendly services to the public. Responsiveness is reflected in the employees’ ability to respond quickly and appropriately to the needs and issues of the community. Regarding accountability, employees demonstrate orderly administrative management, transparent reporting, and openness in disseminating information to the public.